Synthesis of high-quality carbon nanotube fibers by controlling the effects of sulfur on the catalyst agglomeration during the direct spinning process1. Issue 52 (10th June 2015) - Lee, Sung-Hyun; Park, Junbeom; Kim, Hye-Rim; Lee, Jaegeun; Lee, Kun-Hong
<x xml:space="preserve">Abstract</x> The effects of sulfur on the size of iron catalyst particles and synthesized carbon nanotubes (CNTs) were investigated during the direct spinning of CNT fibers.